Artificial magnetic conductor for various antenna applications: An overview. Issue 6 (2nd March 2017) - Dewan, Raimi; Rahim, M.K.A.; Hamid, M.R.; Yusoff, M.F.M.; Samsuri, N.A.; Murad, N.A.; Kamardin, K.
Abstract: Artificial Magnetic Conductor (AMC) is a type of implemented metamaterial in several antennae and microwave design applications. By utilizing the unique characteristics of metamaterials which do not exist naturally, the performance of various microwave devices can be enhanced. This article elaborates on the technical perspective and recent works on AMC for antenna applications. The technical perspective discusses the theoretical aspects, simulation design procedures, and the measurement setup used to characterize the AMC unit cell. Subsequently, various recent works of antenna design that involve the incorporation of AMC are discussed thoroughly. Each of the recent works is highlighted with specific performance enhancements that can be achieved with the introduction of AMC. The conventionally narrow band property of AMC, which is the bandwidth at which the radiation characteristics and directivity of the antenna can be manipulated, is discussed. The property limits the applications of AMC in wideband antenna applications. One of the techniques to improve the narrow band AMC as the ground plane is discussed in detail. The employment of AMC has solved many issues whilst overcoming the typical limitations in conventional antenna designs.